Study on the export-led growth in Malaysian economy / Nor Azaliza Abdullah - Abdullah, Nor Azaliza (2007)
This study examined the relationship between export growth and GDP growth in Malaysian economy using a more comprehensive sample period and a recently developed causal modeling approach by including imports in the system of equations. This study employed the bivariate causality analysis to test for Granger non causality. The variables that used are real exports, real GDP and also real imports. This study using Malaysian time series which cover the period of 1971 until year 2004, and the data were obtained from Asian Development Bank database. All the data are in the real terms, using the GDP deflector. A major finding for this study is that there exist a relationship between exports and economic growth, where supports the hypothesis exports-led growth in Malaysia. Besides that, the growth of import cannot be ignored when there also has a relationship between imports and economic growth. The results suggest that exports and imports have a significant impact on GDP. Malaysia is an open economy and is dependent on international trade for a large part of its economic development.